Agricultural Strike and Massacre in Meena Kandasamy's the Gypsy Goddess - Aafia Mole, R. P. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The article deals with the tragic incident of kilvenmani massacre and the involvement of political parties. Massaccre, rape, labours strike and all forms of brutal violence are involved during the time of agricultural strike. Meena Kandasamy throughout the novel tells about the Dalit agricultural labourers, who live in an inhuman condition. The unrelenting oppression and heart breaking atrocities inflicted upon them by their ruthless upper caste landlords are unpredictable. In this paper I would like to describe how the communist party evolved and what are the changes one can bring out on the issue of caste discrimination.
Keywords: communism; violence; caste discrimination; trauma; Kilvenmani massacre